Transition to thorium fuel cycle on a heavy water moderated molten salt reactor by using low enrichment uranium. (January 2022) - Wu, Jianhui; Chen, Jingen; Zou, Chunyan; Yu, Chenggang; Cai, Xiangzhou; Zhang, Yapeng
Highlights: Transition to thorium fuel cycle on a HWMSR by using low enrichment uranium (LEU) is studied. LEU with U-235 enrichment no lower than 5% can successfully achieve transition on HWMSR. By raising LEU enrichment from 5% to 19.75%, the DT shortens from 58 years to 17.3 years at RT of 10 days. The fuel cycle cost is comparable to that of AP1000 when the RT is longer than 30 days. The material attractiveness of U and Pu increases and decreases respectively as raising LEU enrichment. Abstract: Lacking fissile element (U-233) in nature is a key issue faced by Th-U fuel cycle, and existing available fuels should be taken as starting fuel to convert Th-232 to U-233 to realize transition to thorium fuel cycle. Low enrichment uranium (LEU, U-235 enrichment < 20%) is the most accessible fuel, and has been widely studied as starting fuel to realize transition to Th-U fuel cycle in graphite moderated molten salt reactors. Due to an inevitable introduction of large amount of fertile element U-238, however, this transition way has proven to be almost impossible. Heavy water moderated molten salt reactor (HWMSR) is an innovative molten salt reactor adopting heavy water as the moderator and heavy metal elements dissolved in fluoride salt as the fuel. A high neutron economy resulting from heavy water paves the way for the transition from LEU to thorium fuel cycle. The results obtained from this study indicated that transition can be achieved by using LEU with enrichment no lower than 5%. Raising enrichment would also enhance the breeding performance, but exert negative/positive influences on the attractiveness of uranium/plutonium contained in the fuel salt, decrease the heavy metal utilization efficiency and impose a small impact on the fuel cycle cost.